Cognitive and emotional elements in the teaching and learning process: Thinking, feeling and acting - Solino, Eugenio Gabriel Custódio; Carvalho, Plauto Simão de; Miranda, Sabrina do Couto de (Aprender, 2025)
This work aims to relate different theoretical bases for the development of a foundation that enables the articulation of cognitive and emotional aspects in the teaching and learning process. To this end, a thematic analysis was carried out of the main works of the references that guide this work. David Ausubel and Marco Antonio Moreira are the authors who will underpin the concepts of meaningful learning and critical meaningful learning, respectively. John Mayer and Peter Salovey are the bases used to present emotional intelligence and its potential. To complement these theories, the concepts of Carl Rogers’ humanistic perspective, Albert Bandura’s self-regulation and self-efficacy, and Humberto Maturana’s epistemology of the Biology of Knowing are also used. It was concluded that there are four basic characteristics that must be carefully considered in any action related to teaching and learning. The first is that learning is individual for each agent, the second is that each agent has responsibilities in the learning process, the third is that interactions and adaptability to the environment influence the process, and the last is that proper manipulation of language is essential in all teaching and learning processes.